Rainbow Connection Number Pada Operasi Graf - Yulianti S, Arnasyitha; Dafik, Dafik (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
An edge-colouring of a graph $G$ is rainbow connected if there are $k$ internally vertex-disjoint paths joining them, with no two edges on the path have the same color. Let $G$ be a simple graph and $f$ be an edge coloring, where $f:E(G)→{\{1,2,...,k\},\,\, k\in{N}}$, and the adjacent edges may have the same colour. The rainbow connection numbers of a connected graph G, denoted by $rc(G)$, is a minimal numbers of color $G$ required to make a rainbow connection. This paper discussed rainbow connection for any special graph, namely graph $P_n\otimes H_{2,2}$ and graph $P_3\otimes C_{n}$.}